Nicholas of Cusa: a sketch for a biography - Meuthen, Erich (Catholic University of America Press, 2010)
""Cover""; ""Text""; ""Title Page""; ""Copyright""; ""Contents""; ""List of Illustrations""; ""Acknowledgments""; ""About This Translation""; ""Erich Meuthen: An Appreciation""; ""The World of Cusanus, 1401â€?1464""; ""Preface to the Seventh Edition""; ""Foreword""; ""A Sketch for a Biography""; ""Glossary""; ""Bibliographic Notes on Cusanus Research""; ""Bibliographic Notes on Cusanus Research,1992â€?2005""; ""Index""